2020
DOI: 10.31254/dentistry.2020.5204
|View full text |Cite
|
Sign up to set email alerts
|

Conservative endodontics II: A truss access/ orificeoriented access case series of premolars

Abstract: Strategic dentin preservation is the prime objective of this case report (i.e. leaving a truss of dentin between the 2 cavities thus prepared). Permanent teeth with an indication for endodontic treatment can be treated via the truss access cavity design rather than traditional access cavity protocol using copious irrigation. The teeth were then given post-endodontic restorations. Endodontically treated teeth did not show any post-operative symptoms or any presence of post-operative periapical radiolucency or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Conservative dentistry aims to provide the least invasive treatment possible 33 . In endodontics, access design involving minimum tooth tissue removal has been developed to provide root canal therapy with less removal of tissue structure 34 . A recent study using cone‐beam computed tomography evaluated traditional and conservative access; it concluded that traditional access requires the removal of 9.61 mm 2 of tissue for males and 8.91 mm 2 for females, and conservative access made the removal of 3.4 mm 2 for males and 3.1 mm 2 for females.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative dentistry aims to provide the least invasive treatment possible 33 . In endodontics, access design involving minimum tooth tissue removal has been developed to provide root canal therapy with less removal of tissue structure 34 . A recent study using cone‐beam computed tomography evaluated traditional and conservative access; it concluded that traditional access requires the removal of 9.61 mm 2 of tissue for males and 8.91 mm 2 for females, and conservative access made the removal of 3.4 mm 2 for males and 3.1 mm 2 for females.…”
Section: Discussionmentioning
confidence: 99%
“…“Truss” AC is a Cons endodontic AC (Conservative Endodontic Access Cavity (CEC)) technique. [ 1 ] Its aim is to keep the dentinal bridge in place between two or more small cavities made to access the canal orifice(s) in each multirooted tooth root. [ 2 ] Separate cavities are formed in the mandibular molars to approach the mesial and distal canal systems, whereas, in maxillary molars, the mesio- and disto-buccal canals are accessed via one cavity, while the palatal canal is addressed through another.…”
Section: T Russ a Ccess C ...mentioning
confidence: 99%
“…[ 2 ] Separate cavities are formed in the mandibular molars to approach the mesial and distal canal systems, whereas, in maxillary molars, the mesio- and disto-buccal canals are accessed via one cavity, while the palatal canal is addressed through another. [ 1 ]…”
Section: T Russ a Ccess C ...mentioning
confidence: 99%
See 2 more Smart Citations